Strengthening Student Discipline through Instructional Strategies in Physics Learning: A Naturalistic Study from Four Pedagogical Perspectives - Dewi, Diah Sari; Farni, Evi Ramna; Suryati, Sri (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to explore the strategies used by physics teachers in building students' discipline within character education. This study offers theoretical insights into discipline formation and practical guidance for teachers to implement character-based strategies in physics classrooms. Methodology: This study used a qualitative naturalistic approach with purposive sampling. Data were collected through participatory observation, semi-structured interviews, and documentation. Tools used include observation sheets, interview guides, and field notes. The data were analyzed using the Miles and Huberman interactive model. Validity was ensured through triangulation techniques and member checking for data verification. Main Findings: The findings show that students' discipline in physics learning was very good. Teachers consistently apply structured strategies, methods, and models that promote punctuality, rule adherence, timely task submission, and practical work discipline. Early communication, consistent rule enforcement, and value reinforcement shaped responsible behavior. Most students felt helped by systematic learning patterns. Teacher strategies were closely linked to students' disciplinary character formation in physics class. Novelty/Originality of this study: This study offers originality by integrating a naturalistic approach to explore teacher strategies in building student discipline through four instructional perspectives: approach, method, model, and strategy. It advances existing knowledge by highlighting value internalization in physics learning, shifting the focus from formal rule enforcement to reflective classroom practices that naturally foster character-based discipline.